Analysis of a two-body floating wave energy converter with particular focus on the effects of power-take off and mooring systems on energy capture - MULIAWAN, Made Jaya; Gao, Zhen; MOAN, Torgeir; Babarit, Aurélien (Journal of Offshore Mechanics and Arctic Engineering, 2013)
International audience The present paper summarizes analyses of a two-body floating wave energy converter (WEC) including the mooring system. An axi-symmetric Wavebob type WEC is chosen as the object of investigation here. However, the PTO system is modeled in a simplified manner as ideal linear damping and spring terms that couples the body 1 and the body 2 motions. The analysis is done using SIMO, a time domain simulation tool which accommodates simulation of multi-body systems with hydrodynamic interactions. In SIMO, docking cone features have been introduced between the two bodies to let them move as per actual operation and fenders are applied to represent end stops. Six alternative mooring configurations are applied to investigate the effect of mooring on power capture. In this paper, the software HydroD using WAMIT for hydrodynamic is used to determine hydrodynamic loads. The analysis is carried out for several regular and irregular wave conditions as representative of operational conditions. Simulations are performed with the purpose to study the effects of power take off (PTO) system, end stops setting and several mooring configurations on power captured by the WEC.